Semiotic Analysis of The Logo and Sign Posts as Found in PT KAI Medan 2024 - Lasma Duma Lestari Hutauruk; Sondang Manik; Rony Arahta Sembiring (Merwin Publisher, 2025)
This research focuses on a semiotic analysis of the logo and directional signs at the PT Kereta Api Indonesia (KAI) Medan Station. Utilizing Peirce's theory, this study identifies nine semiotic sign elements emerging from the analysis, with symbols dominating as the most frequently occurring element. The logo of PT KAI Medan, characterized by the use of dark blue color and a line crossing the letter